2005
DOI: 10.1159/000087505
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Valproate on Sodium and Chloride Urinary Excretion in Rats, Gender Differences

Abstract: Evidence exists indicating that sodium valproate (VPA) increases diuresis in rats. The chloriuretic and natriuretic effect of VPA has not previously been investigated, so the aim of the present study was to define the peculiarities of 24-hour urinary sodium (Na) and chloride (Cl) excretion in young adult Wistar rats of both genders, and to evaluate the effects of VPA. 24-Hour urinary Na, Cl, creatinine and pH levels were measured in 28 control intact Wistar rats and 26 Wistar rats after a single intragastric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
5
17
0
Order By: Relevance
“…The specificity of valproate for GABA suggests that this interaction may be an important mechanism through which sodium valproate (NaVPA) exerts its pharmacological effects [2]. Recently NaVPA has shown to enhance the urinary excretion of sodium (Na + ) and chloride (Cl - ) ions in both genders, but the 24-h chloriduretic response in male rats to NaVPA was significantly higher than in female rats [3]. The effect of NaVPA on potassium ion (K + ) excretion was not yet studied.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of valproate for GABA suggests that this interaction may be an important mechanism through which sodium valproate (NaVPA) exerts its pharmacological effects [2]. Recently NaVPA has shown to enhance the urinary excretion of sodium (Na + ) and chloride (Cl - ) ions in both genders, but the 24-h chloriduretic response in male rats to NaVPA was significantly higher than in female rats [3]. The effect of NaVPA on potassium ion (K + ) excretion was not yet studied.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of thymus weight was induced after prenatal exposure to VPA in male but not in female rat offsprings (Schneider et al, 2008). VPA was shown to enhance the urinary excretion of sodium and chloride ions in Wistar rats of both genders, but the 24-h chloriduretic response was found to be gender-related (Grikiniene et al, 2005;Jakutiene et al, 2007): in male rats the rate of excretion was higher than in female. The intracellular chloride concentration would be one of the critical messengers in cell growth/proliferation and differentiation processes (Hiraoka et al, 2010;Ohsawa et al, 2010;Shiozaki et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…0231; 09-07-2012). The VPA dose was chosen according to literature data on preclinical pharmacodynamic studies of VPA and our own data (Ahmad et al, 2005;Grikiniene et al, 2005;Haley et al, 2005).…”
Section: Experiments Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous results suggested that VPA can decrease APP metabolism in Aβ generation, inhibit SP formation, improve spatial learning, and reduce memory defects in male AD mice [24][25][26]. Evidence indicates that there are genderrelated effects of VPA on sodium and chloride urinary excretion in rats [27] or magnesium urinary excretion in adolescents [28]. The mechanisms of such gender-related differences are not yet clear.…”
Section: Introductionmentioning
confidence: 99%